Resistance Band Exercise Dalam Meningkatkan Kesehatan Lansia A Systematical Review - Yunita Selly Santoso; Hari Kristianto (NERSMID : Jurnal Keperawatan dan Kebidanan, 2020)
Resistance band exercise is a simple, easy sport and its implementation does not require a long time to be used as an alternative sport choice. describe resistance band exercise for elderly health by reviewing it. This research method seeks fullpaper articles via Pubmed, Sciendirect, ebsco, proquest, and scopus according to criteria. The search was conducted in the June period and analyzed using PICO / PICOS. Research results Appropriate articles of kriteia obtained as many as 9 articles published period 2010-2019. The majority of resistance band exercise without the addition of exercise shows an improvement in health status. The majority of the duration of the intervention is more than 4 months, resistance band exercise has good health benefits for the elderly aside from the health side but also the financial side that is likely to be expended if the elderly are sick.